Abiotic constraints override biotic constraints in East African highland banana systems - Wairegi, L.W.I.; Asten, Piet J.A. van; Tenywa, M.M.; Bekunda, Mateete A. (Elsevier, 2010)
Banana is the primary food crop in Uganda, but yields are low due to a complex of abiotic and biotic constraints. However, quantitative information on the importance, interactions, and geographic distribution of yields and constraints is scanty. We monitored yields, biotic and abiotic constraints in 159 plots in Central, South and Southwest Uganda in 2006–2007. About half the plots were on-farm demonstrations that received fertilizer (average 71N, 8P, 32 K kg ha−1 year−1) through a development project, the rest were ordinary farmer fields (i.e. controls). Fresh banana yields in controls were significantly (P ≤ 0.05) higher in Southwest (20 t ha−1 year−1) compared with Central (12 t ha−1 year−1) and South (10 t ha−1 year−1). Demonstrations yielded 3–10 t ha−1 year−1 more than controls. Yield losses were calculated using the boundary line approach. In Central, yield losses, expressed as percentage of attainable yield, were mainly attributed to pests (nematodes 10% loss, weevils – 6%) and suboptimal crop management (mulch 25%). In South, poor soil quality (pH – 21%, SOM – 13%, N-total – 13%, and Clay – 11%) and suboptimal crop management (weeds – 20%) were the main constraints. In Southwest, suboptimal crop management (mulch 16%), poor soil quality (K/(Ca + Mg) − 11%) and low rainfall (5%) were the primary constraints. The study revealed that biotic stresses (i.e. pests, weeds) are particularly important in Central, whereas abiotic stresses (i.e. nutrient deficiencies, drought) dominate in South and Southwest. This study concludes that (i) technologies currently available allow farmers to double yields and (ii) past research efforts have mistakenly neglected abiotic constraints.